Usability Engineering of a Radiological Workstation for Mobile Devices: An Experience Report - Costa, Pedro; von Wangenheim, Aldo; von Wangenheim, Christiane; Inácio, Andrei; de Macedo, Douglas (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2016: Anais do XVI Workshop de Informática Médica, 2016)
Medical imaging is commonly used to diagnose many emergent conditions as well as plan treatments. Digital images can be visualized on almost any computing device that has a screen. These days most devices used to visualize digital images are still desktops. Despite that, the world that surrounds us is evolving to a more mobile environment, therefore, mobile devices are increasingly being incorporated onto Picture Archiving and Communication Systems (PACS). In this paper we describe the usability engineering of a new medical image viewer for iPads as a Teleradiology tool for evaluating CTs, X-Rays, Ultrasounds, etc. First we gathered requirements, after we created a series of prototypes and finally the development of the actual application. The experience resulted in insights into how to develop an appropriate viewer for the specific target end user group. Our results suggest that emergency conditions commonly encountered on CT and MRI can be diagnosed using tablet computers with good agreement with dedicated PACS workstations, accordingly to ACR (American College of Radiology). Shortcomings in application design should be addressed f the potential of tablet computers for mobile Teleradiology is to be fully realized.